CLEC5a-directed bispecific antibody for effective cellular phagocytosis. Issue 1 (31st December 2022) - Kedage, Vivekananda; Ellerman, Diego; Fei, Mingjian; Liang, Wei-Ching; Zhang, Gu; Cheng, Eric; Zhang, Juan; Chen, Yongmei; Huang, Haochu; Lee, Wyne P.; Wu, Yan; Yan, Minhong
ABSTRACT: While antibody-dependent cellular phagocytosis mediated by activating Fcγ receptor is a key mechanism underlying many antibody drugs, their full therapeutic activities can be restricted by the inhibitory Fcγ receptor IIB (FcγRIIB). Here, we describe a bispecific antibody approach that harnesses phagocytic receptor CLEC5A (C-type Lectin Domain Containing 5A) to drive Fcγ receptor-independent phagocytosis, potentially circumventing the negative impact of FcγRIIB. First, we established the effectiveness of such an approach by constructing bispecific antibodies that simultaneously target CLEC5A and live B cells. Furthermore, we demonstrated its in vivo application for regulatory T cell depletion and subsequent tumor regression.